Anionic Polymerizations of Bis(terphenyl) Substituted Butadienes for Precursors of Head‐to‐Head Substituted Polyacetylenes. Issue 12 (18th April 2017) - Yu, Yunhai; He, Junpo
Abstract : Three kinds of butadiene derivatives with m ‐(alkyl)terphenyl substituents at 2, 3‐position are synthesized and used for anionic polymerizations. Subsequently, the precursor polymers are converted into head‐to‐head polyacetylenes via oxidative dehydrogenation. The structure and properties of precursor polymers and their corresponding polyacetylenes are characterized by NMR, gel permeation chromatography, matrix‐assisted laser desorption/ionization time‐of‐flight mass spectroscopy, UV–vis, fluorescence spectroscopy, and thermogravimetric analysis. Abstract : A series of butadiene derivatives with m ‐(alkyl)terphenyl substituents at 2, 3‐position is synthesized and used for anionic living polymerizations. The controllabilities of the polymerizations of these monomers depend on solvent, temperature, and the alkyl groups on the terphenyl rings. In tetrahydrofuran (THF), the polymerization does not occur or proceeds very slowly at −78 °C. In toluene or cyclohexane, the polymerization proceeds smoothly in the presence of a small amount of THF at 40 °C. Monomer with n ‐butyl substituents on the phenyl ring undergoes polymerization in a well‐controlled manner in hydrocarbon solvent with or without THF additive. The resulting narrow disperse polybutadiene derivatives are characterized by using size exclusion chromatography, nuclear magnetic resonance spectroscopy, and ultraviolet spectroscopy. It is found that the polymer chains are formed almost exclusively by 1, 4‐addition. The precursor polymers are converted into polyacetylenes with head‐to‐head regiospecificity by oxidative dehydrogenation using 2, 3‐dichloro‐5, 6‐dicyano‐1, 4‐benzoquinone.